Design of control tools for use in microgrid simulations - Othee, Avpreet Singh, author; Young, Peter M., advisor; Zimmerle, Daniel, committee member; Collins, George, committee member (Colorado State University. Libraries, 2018)
New technologies are transforming the way electricity is delivered and consumed. In the past two decades, a large amount of research has been done on smart grids and microgrids. This can be attributed to two factors. First is the poliferation of internet. Internet today is as ubiquitous as electricity. This has spawned a new area of technology called the internet of things (IoT). It gives us the ability to connect almost any device to the internet and harness the data. IoT finds use in smart grids that allow utiliy companies to deliver electricity efficiently. The other factor is the advancement in renewable sources of electricty and high power semiconductors coupled with their decreasing cost. These new sources disrupt the traditional way of electicity production and delivery, putting an increased focus on distributed power generation and microgrids. A microgrid is different from a utility grid. The difference is in the size of the grid, power level, a variety of possible sources and the way these are tied together. These characteristics lead to some unique control challenges. Today's appliances and consumer goods are powered using a standardized AC power. Thus a microrid must deliver uninterrupted and high quality power while at the same time taking into account the vastly different nature of the microsurces that produce the power. This work describes control system tools for different power converters that will be used in simulating microgrids.\ Simulations are important tool for any researcher. It allows researchers to test their research and theories at a greatly reduced cost. The process of design, testing and verification is an iterative process. Simulations allow a cost effective method of doing research, substituting the actual process of building experimental systems. This greatly reduces the amount of manpower and capital investment. A microgrid consists of several building blocks. These building blocks can be categorized into microsources, energy stores, converters and the loads. Microsources are devices that produce electric power. For example, a photovoltaic panel is a mirosource that produces DC power. Converters act as an interface between microsources and the grid. The constituent chapters in the document describe microsources and converters. The chapters describe the underlying control system and the simulation model of the system designed in Simulink. Some of the tools described are derived from the MATLAB/Simulink Examples library. Original authors of the simulation models and systems have been duly credited. Colorado State University has a vibrant research community. The tools described in this thesis are geared to be used for research into microgrids. The tools are developed in a simulation software called Simulink. The tools would allow future researchers to rapidly build microgrid simulations and test new control system implementations etc. The research described in the thesis builds upon the research by Han on natural gas engine based microgrid. The control tools described here are used to construct a microgrid simulation. The microgrid is built around a natural gas engine. Due to the transport lag in delivering fuel, a natural gas engine exhibits significant deviation in the AC grid frequency when subjected to step load. The microgrid setup along with the control system described here, minimizes the frequency deviation, thus stabilizing the microgrid. Simulation results verify the working of the tools.
Keywords: microgrid; simulink simscape power systems specialized technology; microgrid control; inverter control